Education and Self-Employment: South Asian Immigrants in the US Labor Market - Nabamita Dutta; Saibal Kar; Sanjukta Roy (Institute for the Study of Labor (IZA), 2014)
Does higher educational attainment lead to greater participation in self-employment? Available studies agree and disagree on this subject through various explanations. We invoke an empirical example from the experiences of immigrants moving from poor countries to rich countries. Further, we focus exclusively on the self-employment participation among south Asian immigration in the United States (using IPUMS Data), which the related literature has clearly neglected thus far despite long traditions of successful business ventures. We establish that higher educational attainment for immigrants from south Asia reduces the likelihood of being self-employed. In fact, a South Asian immigrant with higher educational attainment has 10% less chance of being self-employed than one without. In addition, we show that factors such as longer stay in USA and being a male, affect the likelihood of being self-employed positively. However, another interesting finding of our paper is that being a 'citizen immigrant' affects the probability of being self-employed positively. Though citizen immigrants with higher education attainment are less likely to choose self-employment, the probability is relatively higher in comparison to the non-citizen immigrant group with similar levels of education. This trend lends itself to a more than proportionate participation in self-employment by the citizen immigrants and the difference with immigrant non-citizen group becomes statistically significant. These results have various static and dynamic implications for the native labor market in host countries.
Keywords: J11; J15; J24; 330; immigration; occupation; microdata; USA; South Asia